Integrated Approach of Yoga and Naturopathy Treatments for Pain Relief and Quality of Life Enhancement in an Intervertebral Disc Prolapse Patient: A Case Report - J, Jebalin Josco; S, Ishwariyaa; R, Yoga Priya; S, Geethanjali (Indian Journal of Integrative Medicine, 2025)
Intervertebral disc prolapse (IVDP), or herniated disc, is a common cause of chronic pain in the cervical and lumbar spine, often causing nerve irritation, radiating pain, and muscle weakness. Conventional treatments like NSAIDs, muscle relaxants, or surgery are common but may have side effects or complications, prompting interest in complementary approaches like yoga, naturopathy, and acupuncture for pain relief and improved quality of life. A 29-year-old woman with five months of chronic neck pain radiating to the right upper limb and lower back pain radiating to the left lower limb was evaluated. Her MRI showed angular Type-2 Modic changes at L4-L5, bilateral L5-S1 facet arthropathy, diffuse disc bulges at L4-S1, and disc bulges at C3-C6 causing anterior indentation of the spinal cord. Her work, involving long computer hours, contributed to her symptoms. After only partial relief from allopathic treatment, she sought an integrative approach combining naturopathy, yoga, and acupuncture. The 14-day protocol included: Hydrotherapy with a 10-minute ice compress on the spine to reduce inflammation. Yoga therapy, including Sukshma Vyayama (gentle neck exercises) and Shava-Udarakarshanasana series for spinal flexibility and tension relief. Acupuncture at specific points (GB 20, GB 21, UB 25, UB 26, and GV 4), with electrical stimulation on GB-20 and UB-26 for 20 minutes. Partial Swedish massage with hot fomentation to relax neck and back muscles. Isometric strengthening exercises for the neck and lower back. Results showed a significant reduction in pain, improved mobility, and enhanced quality of life, with decreased Visual Analogue Scale (VAS), Neck Pain Disability Index (NPDI), and Oswestry Disability Index (ODI) scores. This integrative, non-invasive approach combining hydrotherapy, yoga, acupuncture, massage, and strengthening exercises proved effective for chronic musculoskeletal pain associated with IVDP. Hydrotherapy helped with inflammation, yoga improved flexibility and mobility, and electroacupuncture provided targeted pain relief by addressing nerve irritation. Massage therapy and strengthening exercises supported muscle relaxation and pain reduction. These findings suggest that integrative therapies may be viable alternatives or complements to conventional treatments for chronic IVDP. Further research with larger populations is recommended to confirm the long-term benefits of this approach for pain management and functional improvement.